DISKRIMINASI ORANG DENGAN HIV/AIDS (Study Kasus Kelompok Dukungan Sebaya (KDS) Smile Plus Temanggung) - Achmad Wisnu Ma'arif (UIN Sunan Kalijaga Yogyakarta, 2019)
This article describes the discrimination of people with HIV / AIDS in the Smile Plus Temanggung Peer Support Group. Besides this research is also to find out the subject responding to discrimination that occurs in the family environment, work environment, and social environment. In this study, the authors used a qualitative method with a case study model. The focus of the study is to examine the discrimination experienced by people with HIV / AIDS. Data collection techniques using observation, interviews, and documentation, with triangulation techniques to test the validity of the data. The results of this study show that of the five research subjects four of them experienced discrimination in the form of direct discrimination and indirect discrimination with sources of discrimination originating from the family and work environment, while in the social environment they did not experience discrimination because the environment did not know their status.Keywords: Discrimination, HIV / AIDS, Peer support groups, Smile Plus